2016
DOI: 10.21767/2572-5394.100009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Mass Index and Body Fat Percentage among Adolescents from Serbian Republic

Abstract: The aim of this study was to determine the relationship between body mass index (BMI) and body fat percentage (% BF) among 1000 healthy adolescents (ages, 15-19 y) from different areas in Serbian Republic (Federation of Bosnia and Herzegovina), during 2014. In this study examined adolescents were divided into four groups after calculating BMI, and after the correlation between BMI and %BF. The obtained results show that there are significantly more (p < 0.01; p < 0.05) boys (ages, 15-18) with a healthy weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…BMI was strongly associated with TBF (R 2 = 0.85 and 0.89 for boys and girls, respectively) and BF% (R 2 =0.63 and 0.69 for boys and girls, respectively), and asserted that BMI as a fatness measure in groups of children and adolescents. Further, Jelena et al (2016) reported the correlation between BMI and %BF was very strong, positive, among young girls (r = 0.975) and boys (r = 0.752). However, this study was not seeking to support the veracity of one anthropometric variable over another, but has reiterated the already well-established linear relationship between such anthropometric indices (i.e.…”
Section: Anthropometric Componentmentioning
confidence: 93%
“…BMI was strongly associated with TBF (R 2 = 0.85 and 0.89 for boys and girls, respectively) and BF% (R 2 =0.63 and 0.69 for boys and girls, respectively), and asserted that BMI as a fatness measure in groups of children and adolescents. Further, Jelena et al (2016) reported the correlation between BMI and %BF was very strong, positive, among young girls (r = 0.975) and boys (r = 0.752). However, this study was not seeking to support the veracity of one anthropometric variable over another, but has reiterated the already well-established linear relationship between such anthropometric indices (i.e.…”
Section: Anthropometric Componentmentioning
confidence: 93%
“…Seseorang bisa memiliki IMT dengan kategori yang sama, namun kategori rerata massa lemak tubuhnya berbeda. Sudut pandang yang sering terbentuk adalah pada IMT yang tinggi maka, massa lemaknya tinggi, begitu pula sebaliknya, meski sebenarnya tidak demikian 9 .…”
Section: Pembahasanunclassified
“…[32] ü Body mass index (BMI) BMI was calculated as the ratio of weight (kilogram) to the square of height (meters). Obesity and overweight were classified according to WHO criteria.…”
Section: Protocolmentioning
confidence: 99%